PENINGKATAN KETERAMPILAN BERBICARA SISWA MENGGUNAKAN METODE BERMAIN PERAN DI KELAS V SEKOLAH DASAR NEGERI 17 PONTIANAK KOTA - Hermaniarsyah, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â Abstract The general problem of this research is to know whether the use of role playing method can improve the speaking skill of VB students of Elementary School 17 Pontianak Kota. The general purpose of this research is to improve the students' speaking skill by using role playing method in grade V students of State Elementary School 17 Pontianak City. The method used in this research is descriptive method with class action research form. Subjects in this study were 36 students of VB class. The procedure in this study consists of four stages: planning, action, observation, and reflection. Data collection techniques used in this study are direct observation techniques and documentary techniques. Data collection techniques used in this study is the observation sheet. The results of this study: (1) Teaching and learning ability of teachers is very good because in the first cycle I meeting is 3.26, at the second meeting rose to 3.4. On the second cyclu of the first meeting to increase to 3.67 and the second increase to 3.86. (2) Teachers who do the learning ability very well because in the first cycle I meeting is 3.3 at the second meeting 3.43. Experienced an increase in cycle II of meeting I was 3.61 and at the second meeting to 3.97. (3) Improving students' speaking skills using role playing method is good because in the first cycle of meeting I the student's average score is 40,97 experiencing improvement in second meeting become 51,04. In the second cycle of meeting I was 65.80 and at the second meeting the increase became 84.55. Keywords: Keywords: speaking skills, role playing methods Â